Ut Amare Discas: Anticipating Friendship in Epistulae Morales 35 - Wilcox, Amanda (Lucius Annaeus Seneca, 2022)
Via an intensive close reading of diction and style in Letter 35, which strives to take equal notice of the metaphorical context of Seneca’s letter collection and the intertextual relationships with texts from other genres that illuminate Seneca’s work, as well as its status as a letter, this analysis demonstrates that the fabric of the letter shows an intense economy of meaning akin to a Horatian ode, and proposes a detailed comparison with Odes 1.9 as an exercise in how the ‘structuring activity’ of the reader is an essential contribution to the literary and philosophical functioning of the letter, contributing alongside the progressor and writer ‘Seneca’ and his addressee ‘Lucilius’ to constitute all three participants in friendship as selves, lovers, and self-lovers, and to anticipate their transformation into true friends.